Struggle for Acceptance - Maintaining External School Evaluation as an Institution in Germany - Anne Piezunka (Historical Social Research, 2019)
In the educational field, evaluations based on standardised indicators play a major role in the determination of evidence-based regulations. To have an effect within a policy field, evaluations based on standardised indicators have to become institutionalised. Nevertheless, very little is known about the strategies that actors apply to institutionalise their procedure and whether these strategies are successful. This paper explores the strategies that German school inspectorates use to maintain external evaluations based on standardised indicators as an institution. The paper draws on educational governance research and institutional work. By conducting expert interviews with staff members of school inspectorates, I show which strategies are used to increase the acceptance by school representatives. Two strategies can be identified: school inspectors try to make less judgements and focus on descriptions of what they have observed (strategy I), and school inspectors give school representatives a greater say when formulating expectations for schools (strategy II). From a governance perspective, these strategies mean that school representatives are perceived as equal partners. They also imply that school representatives do not have to give up any of their autonomy, which is also a necessary condition for the institutionalisation of school inspections.
Keywords: 330; educational assessment; school inspection; institutional work; educational governance